Assessment of K-Ras mutant frequency and micronucleus incidence in the mouse duodenum following 90-days of exposure to Cr(VI) in drinking water - O’Brien, Travis J.; Ding, Hao; Suh, Mina; Thompson, Chad M.; Parsons, Barbara L.; Harris, Mark A.; Winkelman, William A.; Wolf, Jeffrey C.; Hixon, J. Gregory; Schwartz, Arnold M.; Myers, Meagan B.; Haws, Laurie C.; et al. (Mutation research, 2013)
•Cr(VI) did not significantly affect mitotic or apoptotic indices in the duodenum.•Cr(VI) did not increase micronuclei and karyorrhectic nuclei in the duodenal crypts.•Cr(VI) did not increase K-Ras codon 12 GAT mutations in mouse duodenum.•Data support that Cr(VI) induces small intestinal tumors in mice by a cytotoxic MOA. Chronic exposure to high concentrations of hexavalent chromium [Cr(VI)] as sodium dichromate dihydrate (SDD) in drinking water induces duodenal tumors in mice, but the mode of action (MOA) for these tumors has been a subject of scientific debate. To evaluate the tumor-site-specific genotoxicity and cytotoxicity of SDD in the mouse small intestine, tissue pathology and cytogenetic damage were evaluated in duodenal crypt and villus enterocytes from B6C3F1 mice exposed to 0.3–520mg/L SDD in drinking water for 7 and 90 days. Allele-competitive blocker PCR (ACB-PCR) was used to investigate the induction of a sensitive, tumor-relevant mutation, specifically in vivo K-Ras codon 12 GAT mutation, in scraped duodenal epithelium following 90 days of drinking water exposure. Cytotoxicity was evident in the villus as disruption of cellular arrangement, desquamation, nuclear atypia and blunting. Following 90 days of treatment, aberrant nuclei, occurring primarily at villi tips, were significantly increased at ≥60mg/L SDD. However, in the crypt compartment, there were no dose-related effects on mitotic and apoptotic indices or the formation of aberrant nuclei indicating that Cr(VI)-induced cytotoxicity was limited to the villi. Cr(VI) caused a dose-dependent proliferative response in the duodenal crypt as evidenced by an increase in crypt area and increased number of crypt enterocytes. Spontaneous K-Ras codon 12 GAT mutations in untreated mice were higher than expected, in the range of 10−2 to 10−3; however no treatment-related trend in the K-Ras codon 12 GAT mutation was observed. The high spontaneous background K-Ras mutant frequency and Cr(VI) dose-related increases in crypt enterocyte proliferation, without dose-related increase in K-Ras mutant frequency, micronuclei formation, or change in mitotic or apoptotic indices, are consistent with a lack of genotoxicity in the crypt compartment, and a MOA involving accumulation of mutations late in carcinogenesis as a consequence of sustained regenerative proliferation.